A rapid equity focused health impact assessment of a policy implementation plan: An Australian case study and impact evaluation - Kemp Lynn A; Harris Elizabeth; Harris Patrick J; Harris-Roxas Ben F (BMC, 2011)
Abstract Background Equity focused health impact assessments (EFHIAs), or health equity impact assessments, are being increasingly promoted internationally as a mechanism for enhancing the consideration of health equity in the development of policies, programs and projects. Despite this there are relatively few examples of examples of completed EFHIAs available. This paper presents a case study of a rapid EFHIA that was conducted in Australia on a health promotion policy implementation plan. It briefly describes the process and findings of the EFHIA and evaluates the impact on decision-making and implementation. Methods The rapid EFHIA was undertaken in four days, drawing on an expert panel and limited review of the literature. A process evaluation was undertaken by email one month after the EFHIA was completed. An impact evaluation was undertaken two years later based on five semi-structured interviews with members of the EFHIA working group and policy officers and managers responsible for implementing the plan. A cost estimation was conducted by the EFHIA working group. Findings The EFHIA made both general and specific recommendations about how the health equity impacts of the policy implementation plan could be improved. The impact evaluation identified changes to development and implementation that occurred as a result of the EFHIA, though there was disagreement about the extent to which changes could be attributed solely to the EFHIA. Those responsible considered the recommendations of the EFHIA in the next versions of their ABHI implementation plans. Factors that influenced the impact of the EFHIA included consolidating understandings of equity, enabling discussion of alternatives, and differing understandings of the purpose of the EFHIA. The EFHIA cost US$4,036 to undertake. Conclusions This EFHIA was conducted in a short timeframe using relatively few resources. It had some reported impacts on the development of the implementation plan and enhanced overall consideration of health equity. This case highlights some of the factors and preconditions that may maximise the impact of future EFHIAs on decision-making and implementation.